More about Insecticides - E.K. Hartwig (AOSIS, 1980)
An insecticide is a chemical used to kill insects. Insect control can also include other materials such as repellents, oils, antifeedants and attractants. Ideally, an insecticide would effectively control any target insect exposed to it and would be harmless to man and his domestic animals. It would also be readily available in necessary quantitie s , s table chemically, noninflammable, easily prepared and applied, noncorrosive, non-staining, and would have no undesirable odour.